Evaluation of the hypothalamo-pituitary-adrenal axis using the cortisol awakening response test in patients with type 1 diabetes mellitus with and without depression: Multicenter Argentine Study (EMA-1) - Adriana Álvarez; Andrea Kozak; Lucas Costa; Guillermo Alzueta; Juan Bauchi; Claudia De Boni; Guillermo Dieuzeide; Olga Escobar; Teresita García; Patricia Mascaró; Olguita Vera; Diego González; et al. (Revista de la Sociedad Argentina de Diabetes, 2020)
Introduction: depression (DP) has a high prevalence in patients with type 1 diabetes mellitus (DM1) and is associated with negative clinicals consequences like more cardiovascular morbimortality and chronic complications. There are few studies published about the dysregulation of hypothalamo-pituitary-adrenal axis (H-P-A) in DM1 with DP and the relation between DP and the Cortisol Awakening Response Test (CAR) with the glycemic control (GC).